2023
DOI: 10.1590/1809-4430-eng.agric.v43nepe20220137/2023
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF OILSEED RADISH ( Raphanus sativus L. var. oleiformis Pers.) OIL AS A POTENTIAL COMPONENT OF BIOFUELS

Abstract: The growing interest in alternative fuels based on plant oils has led to the search for new plant species. Given this, during 2015-2020, oil from 12 varieties of oilseed radish was studied using standard research protocols. The average content of the dominant fatty acids in the oils studied was: [cis-9] oleic (C 18:1) 33.95% (Cv = 14.2%), [cis-9,12] linoleic (C 18:2) 16.20% (Cv = 20.8%), [cis-13] erucic (C 22:1) 15.18% (Cv = 17.9%), [cis-9, 12, 15] α-linolenic (C 18:3) 13.33% (Cv = 18.5%) and palmitic (C 16:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
4
1
Order By: Relevance
“…The crude oil saponification value (132 ± 1.6 mg KOH/g) is somewhat lower than those reported in the literature for FRSOs, as well as lauric acid-rich oils (Tsytsiura, 2023;Zhang et al, 2016).…”
Section: Physicochemical Properties Of Frsocontrasting
confidence: 66%
See 1 more Smart Citation
“…The crude oil saponification value (132 ± 1.6 mg KOH/g) is somewhat lower than those reported in the literature for FRSOs, as well as lauric acid-rich oils (Tsytsiura, 2023;Zhang et al, 2016).…”
Section: Physicochemical Properties Of Frsocontrasting
confidence: 66%
“…In this study, FRSOs have lower (Faria et al, 2018;Valle et al, 2009) and higher (Zhao et al, 2016) C18:3 levels than the exceptional oils from Brazil and China, indicating the complex diversity in FRSO fatty acid composition. Polaczek & Kura nska, 2022; Shah et al, 2013;Tsytsiura, 2023;Valle et al, 2009Valle et al, , 2010Zhang et al, 2016). Variations regarding acidity, that is, higher acid values, are linked to the amount of polyunsaturated fatty acids (Knothe et al, 2005).…”
Section: Fatty Acid Composition Of Frsomentioning
confidence: 99%
“…Vegetable oils with free fatty acids, high degrees of unsaturation, and high viscosity are undesirable for fuel production, as these properties are transferred to biodiesel [ 9 , 47 ]. The quality of oil from R. sativus plants under water restriction was not affected by this stress, highlighting the potential of this species for biodiesel production, even when grown in regions with low rainfall, compared to other oilseeds such as sunflower [ 49 , 50 ], canola [ 51 , 52 ] and crambe [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its high erucic acid content makes it toxic and, therefore, unsuitable for human consumption [ 6 , 7 ]. Recent studies have identified R. sativus as a potential source of raw materials for the chemical industry [ 8 , 9 ]. Its grains have a high oil content (40–54%) and exhibit physicochemical properties important for biodiesel production [ 1 , 6 , 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…is a typical representative of the Brassicaceae family of multipurpose use (Tsytsiura, 2021). This species is particularly valuable for Ukraine, as it is considered from the point of view of bioenergy supply (Kaletnik and Lutkovska, 2020, Lutkovska and Kaletnik, 2020; Kaletnik et al, 2022;Tsytsiura, 2023Tsytsiura, , 2023a, green manure and biofumigation fertilization systems (Tsytsiura, 2023b) with a high environmental stabilizing effect on intensive soil systems (Berezyuk et al, 2021;Tsytsiura, 2023c) as well as an active component of the biological defense system due to the allopathic effect and active glycoside compounds that can be used in the integrated defense system (Moskalets et al, 2023). The crops of the Brassicaceae family are quite attractive to many species of polyphagous and specific pests.…”
Section: Introductionmentioning
confidence: 99%